Soft Co-Clustering of Data - TUCKER GEORGE J; ROHWER RICHARD; ELLIOTT, JR. FRANK W; KAIN CHRISTOPHER J; JONES STEPHEN C; WEIDERT CRAIG N (2009)
The subject matter of this specification can be embodied in, among other things, a method that includes accessing a data structure that includes information about purchasers, merchants, and financial transactions between the purchasers and the merchants and generating purchaser clusters. Generating purchaser clusters includes clustering the purchasers based on which purchasers make purchases from the same or similar merchants. Each purchaser cluster adopts associations between purchasers belonging to the purchase cluster and merchants from which these purchasers have made purchases. The method also includes generating merchant clusters, where generating the merchant clusters includes clustering merchants based on which merchants are associated with the same or similar purchase clusters and outputting profile information that characterizes typical purchases associated with one or more of the merchant clusters for use in detecting fraudulent transactions.